2019
DOI: 10.2478/jwld-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder engagement in a water user association for agricultural irrigation management in the villages in Indonesia

Abstract: The fostering and empowerment of water user associations (WUAs) has been regulated by the Minister of Agriculture since 2012. However, the implementation of this guideline varies. Some water user associations have achieved improvement, while some others have not. This study discusses how a WUA in the villages that use Bengawan Solo River water has successfully managed the irrigation. One of the factors leading to the success of this WUA is the stakeholder engagement in the agricultural irrigation management an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A five-item Likert scale i.e., very high (5), high (4), moderate (3), low (2) and very low (1) was utilized to support the application of each indicator. Respondents from three irrigation projects provided their perceptions on each indicator using the scale [ [52] , [53] , [54] ]. A consolidated challenge score for each indicator was developed based on the weighted average where the number of respondents ( Table 3 ) is taken as the weights.…”
Section: Methodsmentioning
confidence: 99%
“…A five-item Likert scale i.e., very high (5), high (4), moderate (3), low (2) and very low (1) was utilized to support the application of each indicator. Respondents from three irrigation projects provided their perceptions on each indicator using the scale [ [52] , [53] , [54] ]. A consolidated challenge score for each indicator was developed based on the weighted average where the number of respondents ( Table 3 ) is taken as the weights.…”
Section: Methodsmentioning
confidence: 99%
“…The relationship patterns of political officials and bureaucratic officials showed that political intervention remains present in the bureaucracy and that there has been rampant politicisation of the bureaucracy (Lestari, 2014;Nurprojo, 2014;Rustinsyah & Prasetyo, 2019;Verina., Efendi., & Zetra., 2019). This has encouraged The National Institute of Public Administration (known as LAN) to argue that the relationship pattern between political officials and bureaucratic officials should not merely be a relationship between leaders and subordinates but must display a design of parallel partnership.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…Irrigation needs to be noted to increase agricultural production [10]. However, there is no robust way to allocate, provide access to, and manage water resources in Indonesia which are increasingly scarce [11].…”
Section: Introductionmentioning
confidence: 99%
“…[13][13][13] [13]In their previous research, Julia et al [13] found that there is an authority overlap of stakeholder involvement in irrigation water management in Kampili area due to the different interests and powers of each stakeholder. Rustinsyah and Prasetyo [11] stated that cooperation between the government and water user association (WUA) is needed to succeed the irrigation water management system. In addition, related to stakeholders power and interest issues, Rustinsyah [14] then categorized the power of WUA into four indicators: (1) authority, (2) capability and capacity, (3) credibility, and (4) networking.…”
Section: Introductionmentioning
confidence: 99%